Pengaruh Profitabilitas, Kinerja Lingkungan dan Media Exposure Terhadap Pengukapan CSR Perusahaan Pertambangan - Shintia, Yarah; Merina, Citra Indah (JURNAL ILMIAH EDUNOMIKA, 2024)
This study examines Corporate social responsibility (CSR) in the mining industry in Indonesia, which often results in negative impacts on the environment and society. This study specifically targets publicly listed companies in the mining sector on the IDX during the years 2021-2022. The identified population consists of 59 mining companies. Purposive sampling is employed to select the sample, resulting in 25 mining companies being chosen as the research sample. The study involves observational data collected over two years, namely, the years 2021-2022, comprising a total of 50 observation data points. Secondary data used are derived from the annual reports of mining companies registered on the IDX for the period 2021-2022. The dependent variable in this study is CSR disclosure, while the three independent variables include environmental performance, media exposure, and profitability. The research approach is quantitative analysis, utilizing various quantitative analysis techniques to evaluate the strength of relationships between the dependent and independent variables within the study. The analysis results indicate that profitability has a positive influence on CSR disclosure, while environmental performance and media exposure do not exhibit significant impacts. Keywords: Corporate social responsibility (CSR), CSR disclosure, environmental, mining industry, performance, profitability,